2018
DOI: 10.17116/otorino201883320
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric sensorineural hearing impairment in the adult population

Abstract: The relevance of the problem of a sensorineural hearing loss (ASNL) arises from the necessity of the special approaches to the diagnostics of this condition, the complications accompanying this pathology, and the difficulties encountered in the implementation of the methods designed for hearing rehabilitation of such patients. The objective of the present study was to estimate the prevalence of ASHL among the adult population. The sensorineural impairment of hearing was diagnosed in a total of 2456 (72%) exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In addition, Feder et al reported that 7.7% of Canadian youth aged 6-19 had hearing impairments, less than 2.2% of Canadian youth aged 6-19 had sensorineural HI, and less than 3.5% of Canadian youth aged 6-19 had conductive HI (Feder et al 2017). In addition, in a report of Tufatulin et al, 72% of hearing-impaired adults had sensorineural HI, and among them, 47% had asymmetric HI (Tufatulin et al 2018). These surveillance data demonstrate the importance of considering the native hearing ability of individuals during the design of auditory BCI systems, as we discussed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Feder et al reported that 7.7% of Canadian youth aged 6-19 had hearing impairments, less than 2.2% of Canadian youth aged 6-19 had sensorineural HI, and less than 3.5% of Canadian youth aged 6-19 had conductive HI (Feder et al 2017). In addition, in a report of Tufatulin et al, 72% of hearing-impaired adults had sensorineural HI, and among them, 47% had asymmetric HI (Tufatulin et al 2018). These surveillance data demonstrate the importance of considering the native hearing ability of individuals during the design of auditory BCI systems, as we discussed in the current study.…”
Section: Discussionmentioning
confidence: 99%